Changes in saliva protein profile throughout Rhipicephalus microplus blood feeding - Itabajara da Silva Vaz Junior; Stephen Lu; Antônio F. M. Pinto; Jolene K. Diedrich; John R. Yates; Albert Mulenga; Carlos Termignoni; José Marcos Ribeiro; Lucas Tirloni (Parasites & Vectors, 2024)
Abstract Background When feeding on a vertebrate host, ticks secrete saliva, which is a complex mixture of proteins, lipids, and other molecules. Tick saliva assists the vector in modulating host hemostasis, immunity, and tissue repair mechanisms. While helping the vector to feed, its saliva modifies the site where pathogens are inoculated and often facilitates the infection process. The objective of this study is to uncover the variation in protein composition of Rhipicephalus microplus saliva during blood feeding. Methods Ticks were fed on calves, and adult females were collected, weighed, and divided in nine weight groups, representing the slow and rapid feeding phases of blood feeding. Tick saliva was collected, and mass spectrometry analyses were used to identify differentially secreted proteins. Bioinformatic tools were employed to predict the structural and functional features of the salivary proteins. Reciprocal best hit analyses were used to identify conserved families of salivary proteins secreted by other tick species. Results Changes in the protein secretion profiles of R. microplus adult female saliva during the blood feeding were observed, characterizing the phenomenon known as “sialome switching.” This observation validates the idea that the switch in protein expression may serve as a mechanism for evading host responses against tick feeding. Cattle tick saliva is predominantly rich in heme-binding proteins, secreted conserved proteins, lipocalins, and protease inhibitors, many of which are conserved and present in the saliva of other tick species. Additionally, another remarkable observation was the identification of host-derived proteins as a component of tick saliva. Conclusions Overall, this study brings new insights to understanding the dynamics of the proteomic profile of tick saliva, which is an important component of tick feeding biology. The results presented here, along with the disclosed sequences, contribute to our understanding of tick feeding biology and might aid in the identification of new targets for the development of novel anti-tick methods. Graphical Abstract